Immigrants' Difficulties in Pursuing the American Dream Portrayed in Imbolo Mbue's Behold the Dreamers (2016) - Alfanuari, Alfanuari; Al-Hafizh, Muhammad (English Language and Literature, 2023)
As the national ethos of the United States, the American Dream promises a better life for all Americans, including immigrants. Yet, achieving it has not always been easy for them. This research reveals the difficulties that immigrants experience in pursuing the American Dream. This research employs a descriptive qualitative method, applying Terry Eagleton’s Marxist theory and Jim Cullen’s American Dream theory. This research aims to identify the versions of the American Dream that immigrants want to achieve and examine its difficulties stemming from the capitalist economic system. The results of this research found that there are six versions of the American Dream that immigrants want to achieve, including The Puritan Enterprise, Declaration of Independence, Upward Mobility, The Dream of Equality, The Dream of Home Ownership, and The Coast. This research also found that negative aspects of the capitalist economic system, including inequality, exploitation, alienation, and ideological power, become barriers for immigrants in pursuing the American Dream. The irony lies in perceiving the capitalist system as a means to achieve the American Dream, as it paradoxically creates barriers for immigrants. This research concludes that the American Dream does not truly promise a better life for everyone, especially immigrants facing socio-economic disadvantages.